2023
DOI: 10.1177/1357633x231161774
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in videoconferencing psychotherapy compared to psychotherapy in person: A systematic review and meta-analysis

Abstract: Introduction Videoconferencing psychotherapy (VCP) delivers treatment to individuals with limited access to face-to-face mental healthcare. VCP's effectiveness has been demonstrated for various disorders and therapeutic interventions. However, there is contradictory evidence regarding the therapeutic alliance in VCP as compared to psychotherapy in person (PIP). This meta-analysis examines whether therapeutic alliance differs by psychotherapy's delivery format, namely VCP versus PIP. Methods We searched five da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…Additionally, as patients rated working alliance in the videoconference setting as high, this might also substantially contribute to the effects shown in this study. Previous studies have already shown that the videoconference setting enables the patient and psychotherapist to establish a strong and stable working alliance that is comparable to that in traditional face-to-face treatment [ 63 , 64 ]. Several studies even highlight that a positive working alliance is predictive of substantial decreases in symptomatology [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as patients rated working alliance in the videoconference setting as high, this might also substantially contribute to the effects shown in this study. Previous studies have already shown that the videoconference setting enables the patient and psychotherapist to establish a strong and stable working alliance that is comparable to that in traditional face-to-face treatment [ 63 , 64 ]. Several studies even highlight that a positive working alliance is predictive of substantial decreases in symptomatology [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insgesamt sei laut Erfahrungsberichte psychodynamisch orientierter Psychotherapeut*innen (PD) der therapeutische Prozess mit der einer Präsenztherapie vergleichbar [5]. Auch die therapeutische Beziehung im Videosetting stellt sich in aktuellen Studien, als mit dem Präsenzsetting vergleichbar heraus [10][11][12]. Quantitative Untersuchungen, welche die Effektstärken von VP mit dem F2F-Setting in der psychodynamischen Psychotherapie vergleichen, fehlen jedoch nahezu vollständig.…”
Section: Introductionunclassified
“…Furthermore, there is debate regarding the relational limitations and preservation of the therapeutic alliance in VCP (Norwood et al, 2018; Weinberg, 2020). Updated results showed no difference in the therapeutic alliance in VCP as compared to in‐person psychotherapy (Seuling et al, 2023). On the contrary, clinicians' perspectives on the therapeutic relationship in VCP has been found to be less positive than that of clients (Cataldo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%